Rural water suppliers and efficiency: Empirical evidence from East and West Germany - Johannes Sauer (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2004)
This discussion paper attempts the investigation of inefficiency with respect to water suppliers in rural areas of East and West Germany. This is done by using a nonradial measure of input-specific allocative inefficiency based on the demand system derived from a flexible cost function for the variable inputs labour, energy and chemicals. Distributional dependency with respect to the composed error term is reduced. The cost structure is modelled by applying a modified symmetric generalized McFadden functional form and the imposition of concavity restrictions as required by economic theory. Data on 47 rural water suppliers was collected by a written survey in 2002/2003. The applied second order flexible functional form performs well in the estimations. Efforts towards increasing suppliers? allocative efficiency should focus on the relatively inefficient usage of the inputs energy and chemicals. With exception of the category ?size? the measures of input specific allocative inefficiency are found to be superior to those of overall allocative inefficiency. No significant difference between the efficiency of East and West German suppliers was found. Widely assumed economies of scope for the joint production of water and sewage services as well as vertically integrated utilities are not confirmed by the results. The positive correlation between firm size and overall efficiency finally suggests negative effects on efficiency by the legally set supplying areas. – – Das vorliegende Diskussionspapier untersucht die relative Ineffizienz von Wasserversorgern in ländlichen Regionen Ost- und Westdeutschlands. Hierzu wird ein faktorspezifisches Maß allokativer Ineffizienz auf der Grundlage des Input-Nachfragesystems einer flexiblen Kostenfunktion für die variablen Inputs Arbeit, Energie und Chemikalien angewandt. Die Abhängigkeit des stochastischen Fehlerterms von der Wahl spezieller Verteilungsannahmen wird hierdurch reduziert. Die grundlegende Kostenstruktur eines ländlichen Wasserversorgers wird anhand einer modifizierten, symmetrischen und verallgemeinerten McFadden Kostenfunktion modelliert. Die von der ökonomischen Theorie geforderten Konkavitätsbedingungen können so global berücksichtigt werden. Der verwandte Datensatz für 47 Wasserversorgungsunternehmen in ländlichen Regionen Deutschlands wurde mittels einer schriftlichen Umfrage in 2002/2003 erhoben. Die angewandte und flexibel zweiten Grades funktionale Form liefert effiziente und konsistente Schätzergebnisse. Maßnahmen zur Verbesserung der Effizienz sollten demnach den ineffizienten Einsatz der Faktoren Energie und Chemikalien fokussieren. Mit Ausnahme der Kategorie ?Unternehmensgröße? konnte eine statistische Überlegenheit der inputspezifischen Effizienzmaße festgestellt werden. Ein signifikanter Unterschied in der Effizienz ost- und westdeutscher ländlicher Versorger liegt demnach nicht vor. Gemeinhin unterstellte ökonomische Vorteile einer Verbundproduktion von Wasser- und Abwasserleistungen sowie solche infolge einer vollständig integrierten Unternehmensform werden empirisch nicht bestätigt. Die positive Korrelation zwischen Unternehmensgröße und allgemeiner Effizienz legt schließlich negative Effizienzeffekte der rechtlich kodifizierten Versorgungsgebiete nahe.
urn:nbn:de:gbv:3:2-22252
Keywords: D24; C31; Q25; 330; Ländliche Wasserversorgung; flexible funktionale Form; inputspezifische allokative Effizienz; Rural water supply; flexible functional form; input-specific allocative efficiency; Wasserversorgung; Abwasserwirtschaft; Ländlicher Raum; Wirtschaftliche Effizienz; Allokationseffizienz; Vergleich; Schätzung; Neue Bundesländer; Alte Bundesländer; Deutschland